Apprehending the Transport Network Vehicle Service: Apparatgeist and the (Re)Production of Practices in the Sharing Economy - Codera, William Barry (Archīum Ateneo, 2021)
The emergence of Transport Network Companies (TNC) in the Philippines introduced technology-mediated sharing practices via smartphone applications and private car services. Using Apparatgeist and practice theories, this study used a qualitative approach to examine how such technology-mediated sharing practices produce and reproduce the everyday practices of drivers and riders in an urban area like Metro Manila. These practices include understandings, meanings, images, bodily and mental activities, expertise, as well as material artifacts, objects, and infrastructures. At the center of this study is the materiality of smartphone use in the case of the Transport Network Vehicle Service (TNVS), which complements the TNCs” technological platforms by providing “partner drivers” or transportation services. The study conducted twenty-one semi-structured interviews with partner drivers selected through theoretical sampling procedures to capture partner drivers' diversity. The study shows that the skills and competencies afforded by smartphones facilitate the engagement of the partner drivers in the ride-sharing economy. Initial and subsequent meanings attached to smartphone technology affect its design and implementation by the TNCs and its significance accorded to them by users, non-users, and anti-users. However, the function of the smartphone is not mainly deterministic because it afforded the partner drivers the agency to decide what is best for them and reproduce ride-sharing practices that enable their goals.